1998
DOI: 10.1128/iai.66.9.4484-4490.1998
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of HLA-B27 Peptide Presentation after Infection of Transfected Murine L Cells byShigella flexneri

Abstract: Shigella flexneri is a triggering agent for reactive arthritis in HLA-B27-susceptible individuals. Considering the intracellular multiplication of bacteria, it seems likely that bacterial peptides may be presented by the major histocompatibility complex (MHC) class I pathway. To examine this hypothesis, we infected HLA-B*2705- and/or human β2-microglobulin-transfected murine L-cell lines with M90T, an invasive strain of S. flexneri. Bacterial infection induced no detectable modifications in the biosynthesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…15 Changes in the B27-bound peptide repertoire were also reported in L cells infected with Shigella flexneri. 16 In contrast, in the lymphoid cell line C1R, the HLA-B27-bound peptide repertoires from S. typhimurium-infected and non-infected cells are very similar. 1,17,18 Nevertheless, B27-restricted bacteria-specific CTLs isolated from synovial fluid of ReA patients killed Salmonella-infected HLA-B27-C1R targets, 19 suggesting that small amounts of bacterial peptides were presented by HLA-B27 on these cells.…”
Section: Abstract: Antigens; Arthritis; Peptides; Proteasome; Salmonellamentioning
confidence: 95%
See 1 more Smart Citation
“…15 Changes in the B27-bound peptide repertoire were also reported in L cells infected with Shigella flexneri. 16 In contrast, in the lymphoid cell line C1R, the HLA-B27-bound peptide repertoires from S. typhimurium-infected and non-infected cells are very similar. 1,17,18 Nevertheless, B27-restricted bacteria-specific CTLs isolated from synovial fluid of ReA patients killed Salmonella-infected HLA-B27-C1R targets, 19 suggesting that small amounts of bacterial peptides were presented by HLA-B27 on these cells.…”
Section: Abstract: Antigens; Arthritis; Peptides; Proteasome; Salmonellamentioning
confidence: 95%
“…It has been reported that infection of HeLa cells by S. typhimurium results in an increase of the inducible subunit β 1 i, and concomitant changes in the HLA‐B27‐bound peptide repertoire 15 . Changes in the B27‐bound peptide repertoire were also reported in L cells infected with Shigella flexneri 16 . In contrast, in the lymphoid cell line C1R, the HLA‐B27‐bound peptide repertoires from S. typhimurium ‐infected and non‐infected cells are very similar 1,17 , 18 .…”
Section: Introductionmentioning
confidence: 90%
“…It might be caused by changes in the peptide repertoire presented on the cell surface 22 . In another in vitro study, Shigella infection did not down‐regulate the expression of HLA‐B27 but induced clustering of HLA‐B27 molecules during macropinosytosis and alterations in the peptide presentation by HLA‐B27 23 …”
Section: Discussionmentioning
confidence: 95%